The CasP Project: Past, Present, Future - Jonathan Nitzan; Shimshon Bichler (Review of Capital as Power, 2018)
The study of capital as power (CasP) began when we were students in the 1980s and has since expanded into a broader project involving a growing number of researchers and new areas of inquiry. This paper provides a bird's-eye view of the CasP journey. It explores what we have learned so far, reviews ongoing research, and suggests future trajectories – including the coevolution of Concepts of Power–Modes of Power (COP-MOPs); the origins of capitalized power; the state of capital; finance as the symbolic creordering of capitalism; the role of labour, production and waste; the capitalized environment; and the need for post-capitalist accounting.
Keywords: P16; 330; capital as power; capitalist mode of power